2003
DOI: 10.1007/s00299-003-0648-z
|View full text |Cite
|
Sign up to set email alerts
|

Early antibiotic selection and efficient rooting and acclimatization improve the production of transgenic plum plants ( Prunus domestica L.)

Abstract: We describe here an improved system for routinely developing transgenic plum plants (Prunus domestica L.) through the use of Agrobacterium tumefaciens. The production of non-transformed "escapes" has been virtually eliminated, and rates of plant establishment in the greenhouse have been dramatically improved. The system is based on the regeneration of shoots from hypocotyls extracted from mature seed. The shoot regeneration medium is Murashige and Skoog (MS) salts and vitamins supplemented with 7.5 microM thid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(26 citation statements)
references
References 28 publications
0
25
1
Order By: Relevance
“…Medium supplemented with thidiazuron (TDZ) 7.5 μM in combination with indole-3-butyric acid (IBA) 0.25 μM has been used for shoot regeneration, with a transformation effi ciency of 1.2% (Scorza et al, 1994;González-Padilla et al, 2003). Petri et al (2012) reported 42% transformation effi ciency increase using 9 μM 2,4-dichlorophenoxyacetic acid (2,4-D) for three days during co-cultivation, followed by a regeneration medium containing TDZ (7.5 μM) and kanamycin 80 mg L-1 as selective agent.…”
Section: Genetic Transformationmentioning
confidence: 99%
“…Medium supplemented with thidiazuron (TDZ) 7.5 μM in combination with indole-3-butyric acid (IBA) 0.25 μM has been used for shoot regeneration, with a transformation effi ciency of 1.2% (Scorza et al, 1994;González-Padilla et al, 2003). Petri et al (2012) reported 42% transformation effi ciency increase using 9 μM 2,4-dichlorophenoxyacetic acid (2,4-D) for three days during co-cultivation, followed by a regeneration medium containing TDZ (7.5 μM) and kanamycin 80 mg L-1 as selective agent.…”
Section: Genetic Transformationmentioning
confidence: 99%
“…Approximately 45 and 68% of shoots of 'Shiro' and 'Early Golden' produced roots, respectively ( Table 3). The rooting efficiency was relatively high compared to that of P. domestica (Gonzalen-Padilla et al 2003, Tian et al 2007 on the regular rooting medium. Shoots with developed roots were transferred to Magenta boxes containing the same medium, and plantlets were developed (Fig.…”
Section: Resultsmentioning
confidence: 83%
“…These include cotyledons, hypocotyls, and young leaves (Miguel and Oliveira 1999;Tang et al 2002;Gonzalen-Padilla et al 2003;Pérez-Clemente et al 2004). However, regeneration appeared to be explant specific for a Prunus species.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To get this procedure, 1-phenyl-3-(1,2,3-thidiazol-5-il) urea (thidiazuron, TDZ) at 7.5 µM and indole-3-butyric acid (IBA) at 0.25 µM were applied to the explants in order to regenerate Agrobacterium-mediated transformed hypocotyl segments. The hypocotyls based system was later improved by González-Padilla et al (2003); these authors described a reduction in the total number of regenerated shoots without affecting the transformation rate by application of early selection (80 mg/L of kanamycin and 300 mg/L of Timentin) during shoot regeneration in a medium consisting on half-strength MS salts and vitamins supplemented with 5 mM -naphthaleneacetic acid (NAA) and 0.01 mM kinetin. From these works, new improvement was made in the diploid species Prunus salicina.…”
Section: Genetic Transformation Of Plums In the Waiting For A Peach Tmentioning
confidence: 99%